Govorica kot prostor filozofije, filozofija kot kraj govorice - Komel, Dean (Slavistična revija, 2014)
The relationship between language and philosophy is in many ways being concealed rather than revealed. That fact necessitates a definition of "language" and "philosophy" on the one hand, and of "space" and "location" of their mutual conditioning and enabling, on the other. However, even the questions involved in formulation of an appropriate philosophical definition or, rather, terminology - which in themselves can be rather interesting and substantial - do not cover the entire question of the relationship between philosophy and language. Consequently, special attention needs to be paid to the manner in which various possibilities of verbalizing the meaning arise among different speakers, which ultimately defines the authenticity of philosophical thought. That is also true about "Slovene language in philosophy" and "philosophy in Slovene language".
Keywords: filozofija; govorica; language; philosophy; prostor; Slovene; Slovenian langauge; slovenščina; space; terminologija; terminology